Control Recommendations for Black Medic (Medicago lupulina) Based on Growth and Development in Competition with Strawberry. Issue 2 (6th October 2017) - Sharpe, Shaun M.; Boyd, Nathan S.; Dittmar, Peter J.; MacDonald, Greg E.; Darnell, Rebecca L.; Ferrell, Jason A.
Abstract : Strawberries are an important horticultural crop in Florida. Black medic is among the most problematic weeds within the production system. To better coordinate control measures, black medic growth and development while in competition with strawberry was studied. Twelve plants were randomly selected at each of four field sites in Hillsborough County, FL, in 2014. Plants were repeatedly measured over the growing season for stem length and number of primary branches, flower buds, flowers, and seed clusters. Growing degree days (GDD) were calculated ( T base =0 C) starting from the hole-punch application of the plastic mulch (October 8, 2014, to October 10, 2014) from weather station data generated from the Florida Automated Weather Network. Strawberry height and width increased consistently across all sites, but black medic growth and development varied considerably. Strawberry suppressed black medic growth up to 1, 805 cumulative GDD at three of four sites where black medic remained beneath the strawberry canopy. After 1, 805 GDD, the black medic stems still remained below but experienced exponential growth for total stem length and, in turn, flower buds, inflorescence, and immature seed clusters. Ideal clopyralid spray timing based on susceptible plant size was 890 to 1, 152 GDD. Optimal hand-weeding time frames would likely occur as the plant stems expand beyond the strawberry canopy (to improve visibility) and before flower production to prevent seed return to the seedbank. First seed production was observed at 1, 200 GDD at the earliest site and between 1, 966 to 2, 365 GDD across all the other sites. Overall, consistent trends were observed across sites, but between-site variability was observed that could not be accounted for by differences in temperature.